Do labour market institutions matter? Micro-level wage effects of international outsourcing in three European countries - Ingo Geishecker; Holger Görg; Jakob Roland Munch (Review of World Economics, 2010)
This paper studies the impact of outsourcing on individual wages in three European countries with markedly different labour market institutions: Germany, the UK and Denmark. To do so we use individual-level data sets for the three countries and construct comparable measures of outsourcing at the industry level, distinguishing outsourcing by broad region. We discuss some possible intuitive reasons for why there may be differences in the impact of outsourcing across the three countries, based on labour market institutions.
Keywords: 330; Arbeitsmarkt; Institutionelle Infrastruktur; Outsourcing; Offshoring; Auslandsproduktion; Lohn